Chemical profiling of Cosmos caudatus Kunth possessing antioxidant and α-glucosidase inhibitory activity - W. Ahmad, Wan Nadilah Adibah (2017)
Herbs and medicinal plants are major ingredients in traditional medicine systems or folk medicines for many countries of the world, including Malaysia. The present study aimed to evaluate their antioxidant and antidiabetic potential of some herbs used in Malaysia, and to select the most bioactive amongst the tested plants for further metabolomics study towards identifying their bioactive metabolites. The aqueous ethanolic extracts of five medicinal plant species, i.e Cosmos caudatus, Leucaena leucocephala, Momordica charantia, Pereskia bleo and Averrhoa bilimbi were assayed using DPPH radical scavenging activity, α-glucosidase inhibitory activity and total phenolic contents. C. caudatus gave the highest DPPH radical scavenging activity with IC50 value of 272.46 ± 8.98 μg/mL, and the highest total phenolic content with a value of 0.263 ± 0.02 g GAE/g DW. Meanwhile, the most potent α-glucosidase inhibitory activity was demonstrated also by the leaves of C. caudatus with IC50 of 21.90 ± 3.60 μg/mL, followed by L. leucocephala with IC50 value of 30.80 ± 2.50 μg/mL. The inhibitions were significantly more potent than the positive control, quercetin, with IC50 value of 109.30 ± 4.30 μg/mL. Based on these properties, C. caudatus was selected for further investigation in which the (i) influence of varying the polarity of the extraction solvents, and the (ii) harvesting age of the cultivated herb were correlated to its biological activities (DPPH free radical scavenging and α- glucosidase inhibition activity). An NMR-based metabolomics approach in combination with multivariate data analysis (MVDA) were used to analyse the correlation, while identification of the bioactive metabolites utilized both 2D NMR spectroscopy and LCMS/MS profiling. An EtOH:water (80:20) solvent system was found to be the more preferred extraction solvent for obtaining C. caudatus with significant biological activities. The DPPH free radical scavenging (235.11 ± 29.92 μg/mL), α-glucosidase inhibitory activity (39.18 ± 5.80 μg/mL), and the total phenolic content (0.79 ± 0.09 g GAE/g) of the EtOH:water (80:20) extract were the highest among the C. caudatus leaf extracts. Based on the correlations observed in the NMR metabolomics and detailed NMR spectroscopy and LCMS analysis, were shown to comprise of quercetin derivatives (rutin, quercetin 3-O-glucoside, quercetin 3-O-xyloside, quercetin 3-O-arabinofuranoside and quercetin 3-O-rhamnoside). Meanwhile fatty acid, chlorogenic acid, proline, acetic acid and catechin were the main metabolites present in other, less bioactive C. caudatus leaf extracts. The investigation on how age affected the biological activity of the plant, C. caudatus harvested at different stages of growth, spanning from the 6th to the 14th weeks after planting were subjected to the metabolomics study. The results showed that the best quality of plant material, based on biological activities and total phenolic content, was after 10 weeks of growth. Cluster analysis, using PCA, of the EtOH:water (80:20) extracts prepared from various ages of C. caudatus, separated the 10, 12 and 14 weeks samples from the younger 6 and 8 weeks samples by PC1. Meanwhile, an analysis using PLS, showed strong correlation between 10, 12 and 14 weeks old samples with the and DPPH free radical scavenging and α-glucosidase inhibition activities, as well as the phenolic contents, which formed the basis of the conclusion that the best quality C. caudatus material is obtainable after 10 weeks of growth. The differentiating factors of the discriminative analysis were the chemical shifts for quercetin derivatives and rutin, which were found to be higher in the 10, 12 and 14 weeks old samples. This was further supported by the relative quantification of the metabolites, where higher concentrations of quercetin derivatives including rutin were detected in the 10 weeks old plants, while the levels were observed to decrease as the plant aged to the 12nd and up to the 14th weeks. Relatively lower concentrations were reported for other components such as fatty acid, chlorogenic acid, proline, acetic acid and catechin. Further support for the identification of bioactive metabolites was obtained using LCMS analysis. For the analysis, the EtOH:water (80:20) leaf extract was first solvent partitioned and tested for bioactivity. The EtOAc and BuOH fractions of the C. caudatus extract showed the highest bioactivities with TPC (0.72 g GAE/g DW and 0.60 g GAE/g DW), DPPH radical scavenging activity (255.20 μg/mL and 257.61 μg/mL) and α- glucosidase inhibitory activity (40.90 μg/mL and 74.84 μg/mL), respectively. Both fractions were found to be bioactive and further metabolite profiling using LCMS/MS revealed the presence of six phenolic compounds were detected in EtOAc fraction i.e rutin, quercetin 3-O-galactoside, quercetin 3-O-glucoside, quercetin 3-O-xyloside, quercetin 3-O-arabinofuranoside and quercetin 3-O-rhamnoside. The same metabolites, except for quercetin 3-O-galactoside, were also detected in the BuOH fraction. It’s showed that the flavonoids glycosides were the responsible compounds that contribute to the free radical scavenging and lowering the glucose effects of C. caudatus leaves. Interestingly, in the present study, quercetin 3-O-xyloside in C. caudatus extracts was reported for the first time. On the overall, the results of the current study showed that the EtOH:water (80:20) are the best extraction solvent system for obtaining C. caudatus with significant biological activities. Meanwhile, the 10th weeks old plant (before the flowering stage) was the best harvesting age to yield potentially valuable of antioxidant and α-glucosidase inhibitory activities in C. caudatus. Hence, this plant can be suggested as a potential natural source of antioxidant and antidiabetic compounds for the prevention or the treatment of diabetes and its complications. However, the use of this plant as an alternative remedy for diabetes requires more extensive studies and isolation of the bioactive compounds and its safety and efficacy evaluation on human subjects.